UTILISATION OF EVOLUTION ALGORITHM IN PRODUCTION LAYOUT DESIGN - KRAJČOVIČ, Martin; GRZNÁR, Patrik (Applied Computer Science, 2017)
The need for flexibility of layout planning puts higher requirements for utilisation of layout and location problem solving methods. Classical methods, like linear programming, dynamic programming or conventional heuristics are being replaced by advanced evolutionary algorithms, which give better solutions to large-scale problems. One of these methods are also genetic algorithms. This article describes the genetic algorithm utilisation in the production layout planningunder the terms of the digital factory concept.